2013
DOI: 10.1111/1477-8947.12015
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for sustainable tourism at the Jiuzhaigou World Natural Heritage site in western China

Abstract: Although modern mass tourism in China has a history of only about 30 years, the market has expanded quickly. Endowed with the spectacular scenery of turquoise water lakes and marvelous waterfalls, Jiuzhaigou is one of the most visited tourist destinations in China. Between 1984 and 2012, the region witnessed a tourism growth of 130 times, resulting in extreme economic and environmental impacts. The fast increasing and large tourist population in the limited area has caused many changes in the local environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…Leask [38] identified a challenge as being that there were multiple methods used to measure effectiveness by different stakeholders in accordance with their individual priorities. Another significant challenge was that as well as capacity building, strategic leadership and revenue management, heritage managers are required to focus on cultural sustainability, and its heritage [24,25,50,51]. In this research, despite incorporating all of these elements into their roles, historic building custodians, managers and event managers listed a number of practical management challenges, namely: Technology, staff management, logistics between events, and communication amongst different departments, confirming the findings of previous research into visitor attraction management within heritage contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leask [38] identified a challenge as being that there were multiple methods used to measure effectiveness by different stakeholders in accordance with their individual priorities. Another significant challenge was that as well as capacity building, strategic leadership and revenue management, heritage managers are required to focus on cultural sustainability, and its heritage [24,25,50,51]. In this research, despite incorporating all of these elements into their roles, historic building custodians, managers and event managers listed a number of practical management challenges, namely: Technology, staff management, logistics between events, and communication amongst different departments, confirming the findings of previous research into visitor attraction management within heritage contexts.…”
Section: Discussionmentioning
confidence: 99%
“…As well as promotion, strategic leadership and revenue management, historic building managers are required to focus on cultural sustainability, and heritage [24][25][26], which adds a complexity to the staging of events not faced by other venues, in particular regarding sustainability. Historic buildings, along with castles, visitor attractions, boats, sports stadiums and galleries have been classified as 'unusual venues' [27], indicating that their use does not fall within the standard overview of the events management literature.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Gu et al . () observed conflict between natural attraction areas and local economic development in Jiuzhaigou, China, with the influx of visitors exceeding its carrying capacity, causing degradation of the wetland, vegetation and biodiversity. Similarly, in Florida, Klein et al .…”
Section: Discussionmentioning
confidence: 99%
“…Even ecotourism that exceeds the carrying capacity could have negative impacts on wetland flora and fauna. For instance, Gu et al (2013) observed conflict between natural attraction areas and local economic development in Jiuzhaigou, China, with the influx of visitors exceeding its carrying capacity, causing degradation of the wetland, vegetation and biodiversity. Similarly, in Florida, Klein et al (1995) observed that migrant birds were highly sensitive to human disturbance, and suggested guided tours and the creation of low disturbance zones as an alternative management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Geopark Merangin Jambi mencakup sekitar 1.551 km 2 bagian selatan Kabupaten Merangin yang secara fisiografis berada di bawah wilayah transisi antara Pegunungan Barisan dan Dataran Rendah Rendah Timur (Fitri & Wahyudi, 2018 (Gu et al, 2013;Liu et al, 2013;Hammen et al, 2018;Bian et al, 2010;Liang & Yang, 2019;Yang & Zhang, 2018;Scheible et al, 2008). Geopark merupakan salah satu inovasi dalam dunia pariwisata sehingga dibutuhkan inovasi pengembangan agar dapat maksimal memberikan manfaat bagi wisatawan maupun pemerintah dan pihak swasta lainnya (Ioppolo et al, 2013).…”
Section: Metode Penelitianunclassified